Решите уравнение: (2y-3)(3y+1)+2(y-5)(y+5)=2(1-2y)²+6y.

0 голосов
82 просмотров

Решите уравнение:

(2y-3)(3y+1)+2(y-5)(y+5)=2(1-2y)²+6y.


Алгебра (289 баллов) | 82 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

(2y-3)(3y+1)+2(y-5)(y+5)=2(1-2y)²+6y

6y^2+2y-9y-3+2(y^2+5y-5y-25)=2(1-4y+4y^2)+6y

6y^2-7y-3+2y^2-50=2-8y+8y^2+6y

8y^2-8y^2-55=5y

-55=5y

y=-11

 

(317 баллов)
0 голосов

(2y-3)(3y+1)+2(y-5)(y+5)=2(1-2y)²+6y

6y²-9y+2y-3 + 2y² - 50 = 2 - 8y + 8y² + 6y

-7y + 2y = 2 + 3 + 50

5y = - 55

 y = -11 

 

(12.0k баллов)